The board chairman's characteristics and financial stability of Malaysian-listed firms - Mujeeb Saif Mohsen Al-Absy (Cogent Business & Management, 2020)
This study examines the association between the board chairman's (BC's) characteristics (independence, age, ethnicity, tenure, family membership, dual chair with nomination committee (NC), dual chair with remuneration committee (RC)) and the firm's financial stability. The Altman (1993) Z-Score indicator was used to determine the financial stability of Malaysian suspect-listed firms, i.e., firms with lowest positive earnings for the years 2013-2015. Ordinary Least Square regression indicates that only the age and tenure of the BC are associated with high financial stability. This means that the chairman's age and tenure could protect the company against financial distress. However, the results showed a negative effect of the BC's ethnicity, family membership and dual chair with the NC on the firm's financial stability. These results, in general, are similar to the Feasible Generalized Least Squares regression and other robustness tests. This study is the first to investigate the influence of the board chairman's characteristics on the firm's financial stability. Thus, it alerts policymakers, firms and their stakeholders, as well as researchers, to the importance of strengthening the board chairman's characteristics to protect the company against financial distress, especially in emerging countries such as Malaysia, where it has been observed that the board chairman attempts to dominate the entire firm's decisions.
Keywords: 650; board chairman; family membership; nomination committee; remuneration committee; financial stability; Malaysia